Valve-sparing David procedure via minimally invasive access does not compromise outcome - Shrestha, Malakh; Kaufeld, Tim; Shrestha, Pamila; Martens, Andreas; Rustum, Saad; Rudolph, Linda; Krüger, Heike; Arar, Morsi; Haverich, Axel; Beckmann, Erik (Frontiers in Cardiovascular Medicine, 2022)
Objectives. Aortic valve sparing-aortic root replacement (David procedure) has not been routinely performed via minimally invasive access due to its complexity. We compared our results of elective David procedure via minimally invasive access to those via a full sternotomy. Methods. Between 1993 and 2019, a total of 732 patients underwent a valve sparing root replacement (David) procedure. Out of these, 220 patients underwent elective David-I procedure (isolated) without any other concomitant procedures at our center. Patients were assigned to either group A (n=42, mini-access) or group B (n=178, full sternotomy). Results. Cardiopulmonary bypass time were 188.5±35.4 minutes in group A and 149.0 (135.5-167.5) in group B (p<0.001). Aortic cross-clamp time were 126.2±27.2 minutes in group A and 110.0 (97.0 – 126.0) in group B (p<0.001). Postoperative echocardiography showed aortic insufficiency ≤ I° in 41 (100%) patients of group A and 155 (95%) of group B. In-hospital mortality was 2.4% (n=1) in group A and 0% (n=0) in group B (p=0.191). Perioperative stroke occurred in 1 (2.4%) patient of group A and 2 (1.1%) patients of group B (p=0.483). Reexploration for bleeding was necessary in 4 (9.5%) patients of group A and 7 (3.9%) of group B (p=0.232). Follow-up was complete for 98% of all patients. The 1-, 2-, 4- and 6-year survival rates were: 97%, 97%, 97% and 97%, in group A (mini-access) and 99%, 96%, 95% and 92% in group B (full sternotomy), respectively. The rates for freedom from valve-related re-operation at 1, 2, 4 and 6 years after initial surgery were: 97%, 95%, 95% and 84% in group A and 97%, 95%, 91% and 90% in group B, respectively. Conclusion. Early postoperative results after David procedure via minimally invasive access are comparable to conventional full sternotomy. Meticulous attention to hemostasis is a critical factor during minimally access David procedures. Long-term outcome including the durability of the reimplanted aortic valve seems to be comparable, too.